Intravenous Lidocaine Significantly Reduces the Propofol Dose in Elderly Patients Undergoing Gastroscopy: A Randomized Controlled Trial - Hu S; Wang M; Li S; Zhou W; Zhang Y; Shi H; Ye P; Sun J; Liu F; Zhang W; Zheng L; Hou Q; et al. (Dove Medical Press, 2022)
Song Hu,1- 3,* Mingxia Wang,2,3,* Siyu Li,2,* Wenyu Zhou,3 Yi Zhang,2 Haobing Shi,2 Pengcheng Ye,2 Jixiong Sun,2 Feng Liu,2 Wei Zhang,2 Li Zheng,3 Qianhao Hou,2 Yue Wang,2 Weixin Sun,2 Yuanli Chen,2 Zhenzhen Lu,4 Zhonghua Ji,2 Lijun Liao,2 Xin Lv,3 Yinglin Wang,2 Xiangrui Wang,2 Hao Yang2,3 1Graduate School, Wannan Medical College, Wuhu, 241002, People's Republic of China; 2Department of Anesthesiology and Pain Management, Shanghai East Hospital, Tongji University School of Medicine, Shanghai, 200120, People's Republic of China; 3Department of Anesthesiology, Shanghai Pulmonary Hospital, Tongji University School of Medicine, Shanghai, 200433, People's Republic of China; 4Department of Biostatistics, Zhongshan Hospital, Fudan University, Shanghai, 200032, People's Republic of China*These authors contributed equally to this workCorrespondence: Hao Yang; Xiangrui Wang, Department of Anesthesiology and Pain Management, Shanghai East Hospital, Tongji University School of Medicine, 150 Jimo Road, Shanghai, 200120, People's Republic of China, Email yanghaozunyi@sina.com; wangxiangruirjyy@sina.comObjective: Propofol-based sedation has been widely used for gastroscopy, but the risk of respiratory suppression in elderly patients should not be overlooked. Intravenous (IV) lidocaine during surgery can reduce the demand for propofol and the incidence of cardiopulmonary complications. We examined whether IV lidocaine reduces the dose of propofol and the occurrence of adverse events during gastroscopy in elderly patients.Methods: We conducted a prospective, single-center, double-blind randomized controlled trial in elderly patients aged ≥ 65 years with ASA I-II. Subjects were randomly assigned to the lidocaine group (Group L, n=70), who received IV 1.5 mg kg− 1 lidocaine followed by a continuous infusion of 4 mg kg− 1 h− 1 lidocaine, or the normal saline group (Group N, n=70), who received an equal volume of saline in the same way.Results: IV lidocaine reduced the total and maintenance propofol dose in Group L (p< 0.001), with no significant effect on the induction dose. The incidence of intraoperative hypoxia (p=0.035), emergency airway management events (p=0.005), duration of gastroscopy (p< 0.05), consciousness recovery time (p< 0.001), and postoperative pain (p=0.009) were all reduced in Group L. Patient (p=0.025) and gastroscopist (p=0.031) satisfaction was higher in Group L. Intraoperative hemodynamic parameters, the respiratory rate, the incidence of sedation-related events and anesthesiologist satisfaction were similar between the two groups.Conclusion: IV lidocaine can significantly reduce the amount of propofol, the incidence of hypoxia and postoperative pain during gastroscopy in elderly patients, with a higher patient and gastroscopist satisfaction.Keywords: lidocaine, propofol, gastroscopy, elderly patient, sedation